La collaboration scientifique et technologique en Amérique du Nord : un point de vue Canadien - David, Charles; Dufour, Paul; Halliwell, Janet (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1993)
Canada, as a country with a small, open economy, faces the immediate challenge of learning to shape dynamic comparative advantage in the emerging international economy. About 75 % of Canada's trade linkages are with the United States, and a very large component of the Canadian experience of « globalization » is driven by North American economic integration. This integration is taking place in the absence of institutions and policy mechanisms to promote and manage science, technology, and innovation relations on a continental scale. Bilateral s & T arrangements centered on the United States presently characterize the North American innovation System. Circumstances in North America pose three sets of challenges to Canadian s & T policy. 1) Science and technology are increasing in importance in international trade, environmental, and social/cultural matters. This means that Canada must learn to improve its management of an increasingly internationalized domestic s & T System. 2) Canada must cultivate mutually beneficial bilateral s & T relationships with its two partners in NAFTA, Mexico and the United States. 3) Canada must identify where its interests lie in the development and governance of trilateral and international rules and arrangements for science, technology, and innovation.